Ic paper on elekta ab - apac´s influence in the future of radiotherapy market - Vieira, Henrique Mendes Diniz (2021)
The following Investment Committee paper focuses on a proposal for a leveraged buy out on Elekta AB, a key player in the global radiotherapy market. In fact, this paper develops as et of value creation strategies, with special focus on Buy-and-Build, reflecting those strategies in a detailed operating model. Subsequently, a capital structure is suggested by assessing past buy out transactions in the health care sector and by leveraging the bank case. Finally, the exit returns are estimated complying with industry threshold and a range of exit strategies are analyzed. Moreover ,exit options are compiled in order to fully maximize ELEKTA’s exit.